Aggregation of Economic Indicators Across Countries : Exchange Rate versus PPP Based GDP Weights - Schulze-Gattas, Marianne; Gulde, Anne. (Washington, D.C. : International Monetary Fund, 1992)
Relative GDP shares are frequently used as weights in aggregations. In order to ensure that these weights reflect countries' shares in real output, GDP data in national currencies should be converted into a common numeraire currency at purchasing power parity (PPP) rates. A review of the empirical evidence on the relationship between exchange rates and prices suggests that market (or official) exchange rates are generally poor proxies for PPP rates. The paper examines the PPP-based GDP data generated by the International Comparison Program and compares aggregations with PPP- and exchange rate-based GDP weights.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet